Workers` workload and productivity in oil palm cultivation in Malaysia - El Pebrian, Darius; Yahya, Azmi; Tan, Chun Siang (American Society of Agricultural and Biological Engineers, 2014)
The agricultural industry in Malaysia, for oil palm in particular, has low technology and labor-intensive production systems rather than modern technology and machine-based production systems. This study examined the workers’ workload and productivity with respect to the estimated human energy expenditure, measured heart rate, and measured production capacity for various operations in the nursery and field stages of oil palm cultivation in Malaysia. The objective of the study was to rank each operation in accordance with its priority for a mechanization program. The operations involved in the nursery and field stages and the tasks within each operation were ranked individually based on the combined DWD-DEM-EXH (duration, heart rate, and energy demand) criteria. Holing the soil in large polybags was found to be the highest priority operation for mechanization in the nursery stage, while planting germinated seeds in small polybags was the lowest priority operation. Lining was found to be the highest priority operation for mechanization in the field stage, while pest control was the lowest priority operation. The established DWD-DEM-EXH Cartesian plots can be an important basis for prioritizing the operations for mechanization and ultimately for formulating a mechanization program for oil palm plantations in Malaysia. More specifically, the results of this study could be used for lightening the workload and improving the performance of oil palm plantation workers.